1993
DOI: 10.1002/jts.2490060209
|View full text |Cite
|
Sign up to set email alerts
|

Changes in outlook following disaster: The preliminary development of a measure to assess positive and negative responses

Abstract: Although the introduction of PTSD (APA, 1980, 1987) has fueled much interest into the psychological sequelae of disaster, little attention has been paid to the more existential changes in outlook many survivors report. Preliminary work on the development of a measure to assess both positive and negative responses to disaster is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
0
6

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(101 citation statements)
references
References 15 publications
4
91
0
6
Order By: Relevance
“…Although, there is growing interest in exploring PTG specifically after exposure to terrorism (Butler et al 2005;Dekel and Nuttman-Shwartz 2009;Hobfoll et al 2006Hobfoll et al , 2007Laufer and Solomon 2006) and war (Macksoud and Aber 1996;Saric et al 1994), there appears to be a lack of consensus regarding the relationship between exposure to traumatic events and such growth, especially with reference to the nature of the traumatic event and the time that has elapsed since the traumatic event (Pat-Horenczyk and Brom 2007;Zoellner and Maercker 2006). While psychological distress due to exposure to terrorism has been generally related to greater PTG (Butler et al 2005;Dekel and NuttmanShwartz 2009;Laufer and Solomon 2006), studies of war, illness and disasters have shown mixed findings: Some have found that PTG is related to lower levels of psychological distress (Evers et al 2001;McMillen et al 1997;Updegraff et al 2002), others have found that PTG is related to greater psychological distress (Lev-Wiesel and Amir 2003;Pargament et al 1998) and some have found no relationship at all (Lehman et al 1993;Joseph et al 1993;Solomon et al 1999). In the present study, we therefore, relate to various risk and protective factors that may explain the different correlations between PTG and psychological distress.…”
Section: Psychological Effects Of Exposure To Terrorismmentioning
confidence: 95%
“…Although, there is growing interest in exploring PTG specifically after exposure to terrorism (Butler et al 2005;Dekel and Nuttman-Shwartz 2009;Hobfoll et al 2006Hobfoll et al , 2007Laufer and Solomon 2006) and war (Macksoud and Aber 1996;Saric et al 1994), there appears to be a lack of consensus regarding the relationship between exposure to traumatic events and such growth, especially with reference to the nature of the traumatic event and the time that has elapsed since the traumatic event (Pat-Horenczyk and Brom 2007;Zoellner and Maercker 2006). While psychological distress due to exposure to terrorism has been generally related to greater PTG (Butler et al 2005;Dekel and NuttmanShwartz 2009;Laufer and Solomon 2006), studies of war, illness and disasters have shown mixed findings: Some have found that PTG is related to lower levels of psychological distress (Evers et al 2001;McMillen et al 1997;Updegraff et al 2002), others have found that PTG is related to greater psychological distress (Lev-Wiesel and Amir 2003;Pargament et al 1998) and some have found no relationship at all (Lehman et al 1993;Joseph et al 1993;Solomon et al 1999). In the present study, we therefore, relate to various risk and protective factors that may explain the different correlations between PTG and psychological distress.…”
Section: Psychological Effects Of Exposure To Terrorismmentioning
confidence: 95%
“…Thus, conceptualizing unethical behavior as a precursor to trauma is consistent with the literature. While most data on trauma and post-traumatic stress disorder are derived from studies of war veterans (Schnurr and Jankowski, 1999;Schnurr et al, 2002), exposure to disasters (Hanson et al, 1995;Joseph et al, 1993;Shrubsole, 1999;Simeon et al, 2003), and victims of violent acts (Gerrity et al, 2001;Kubany et al, 2000), its occurrence need not involve a threat to one's life (Avina and O'Donohue, 2002;Schnurr et al, 2002). In fact, researchers have begun to expand the range of events that are considered traumatic, including corporate downsizing (Moore et al, 2004), humiliation (Lindner, 2001), bullying , and sexual and workplace harassment (Bowling and Beehr, 2006;Schneider et al, 1997).…”
Section: The Trauma Mechanismmentioning
confidence: 99%
“…Seventeen articles assessed VPTG using a validated measure of posttraumatic growth. Eleven articles used a version of the Posttraumatic Growth Inventory (PTGI; Tedeschi & Calhoun, 1996), one used the Positive Changes subscale of the Changes in Outlook Questionnaire (CiOQ; Joseph, Williams, & Yule, 1993), four used the PTGI and CiOQ in combination, and one used the Perceived Benefit Scale (PBS; McMillen & Fisher, 1998). These self-report questionnaires required participants to rate their level of agreement with statements describing various psychological and behavioural changes that can follow traumatic exposure.…”
Section: Measurement Of Vicarious Posttraumatic Growthmentioning
confidence: 99%